Study of Cystoscopic Findings in Patients Presenting with Lower Urinary Tract Symptoms at a Tertiary Care Centre - Subedi, Neeraj; Bhomi, Krishna Kaji; Ansari, Wesh; Khadka, Mohan; Sigdel, Bidhan (Nepal Medical College Journal, 2025)
Lower urinary tract symptoms (LUTS) are a collection of symptoms related to problems with voiding, and storage. They generally arise as a result of abnormalities or inadequate functioning of the prostate, urethra, bladder or sphincters. Hospital based cross sectional descriptive study was conducted in the Urology department of a tertiary care hospital in Kathmandu from July 2024 to December 2024. A total of 121 patients underwent cystoscopy during the study period. The mean age of the patient was 53.93±14.752 years and the most common age group was 41- 50 years. Male patients (81.8%) were more than female patients (18.2%). Obstructive symptoms were more common than irritative symptoms. Hematuria was seen in 16 cases (13.2%) and urinary retention was seen 4 cases (3.3%). Benign enlargement of Prostate (BEP) (37.2 %) was the most common finding in cystoscopy followed by urethral stricture (19.8%). A significant association was observed between age categories and cystoscopic findings in patients presenting with LUTS (p=0.028). Among the patients with BEP, there was a significant association between age categories and BEP. Cystoscopy is a very common procedure for patients presenting with LUTS and to evaluate lower urinary tract diseases such as various pathologies of urethra, prostate and bladder.